The Effect of Organizational Support, Leadership and Motivation for Performance Improvement Tanjung Morawa Office Officers Deli Serdang Regency - Yunita Putri Irwan Somba; Wan Dian Safina; Julianto Hutasuhut (PT Inovasi Pratama Internasional, 2022)
This study aims to determine the effect of organizational support, leadership and motivation on the performance of the Tanjung Morawa sub-district office employee, Deli Serdang Regency. The population in this study were 32 employees who worked at the Tanjung Morawa sub-district office. Samples were processed using saturated sampling, namely taking the entire population to be sampled, namely 32 samples. Data collection techniques using the method of documentation, interviews and questionnaires. The classical assumption test used is the Normality Test, Multicollinearity Test and Heteroscedasticity Test. Data analysis using Multiple Linear Regression Analysis technique. The results of this study indicate that the variables of organizational support, leadership and motivation have an effect on employee performance. The results of this study also show that the variables of organizational support, leadership and motivation simultaneously affect employee performance.